Suma de palabras con poder : Elogio al Prof. Dr. Diego Valadés - Ferreyra, Raúl Gustavo (2015)
"Written version of the oral presentation given on August 27, 2015, during the awarding of the honorary doctorate from the University of Buenos Aires to Diego Valadés. The ceremony took place in the Red Room of the Faculty of Law."